2022
DOI: 10.3390/ijerph20010693
|View full text |Cite
|
Sign up to set email alerts
|

Autistic Traits, Arousal, and Gender Features in a Nonclinical Sample of Italian Adolescents

Abstract: (1) Background: Subthreshold autism is a sub-clinical pattern of autism spectrum disorder-like (ASD-like) traits, including poor social skills, cognitive rigidity, anxiety, and aloofness. These ASD-like traits are significantly more prevalent among parents and relatives of participants with autism; however, evidence suggests that subclinical autistic traits are not restricted to the family members of individuals with autism but rather are continuously distributed in the general population. Though the autistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Although the hallmark of ASD is a persistent deficit in engaging in social interactions, it is worth noting that a formal diagnosis of ASD also requires the presence of restricted or repetitive behaviors or activities (American Psychiatric Association 2013 ). Atypical sensory processing in ASD individuals has been extensively documented for a wide range of domains, including auditory, touch, vision, and social stimuli (Marco et al 2011 ; O’Connor 2012 ; Nomi and Uddin 2015 ; DeBoth and Reynolds 2017 ; Balasco et al 2020 ; Chung and Son 2020 ; Iannuzzo et al 2022 ). Such sensory processing differences can pose challenges for individuals with ASD in effectively processing and integrating sensory information, thereby likely impacting their ability to comprehend and respond appropriately to stimuli within their PPS.…”
Section: Pps In Pathological Conditionsmentioning
confidence: 99%
“…Although the hallmark of ASD is a persistent deficit in engaging in social interactions, it is worth noting that a formal diagnosis of ASD also requires the presence of restricted or repetitive behaviors or activities (American Psychiatric Association 2013 ). Atypical sensory processing in ASD individuals has been extensively documented for a wide range of domains, including auditory, touch, vision, and social stimuli (Marco et al 2011 ; O’Connor 2012 ; Nomi and Uddin 2015 ; DeBoth and Reynolds 2017 ; Balasco et al 2020 ; Chung and Son 2020 ; Iannuzzo et al 2022 ). Such sensory processing differences can pose challenges for individuals with ASD in effectively processing and integrating sensory information, thereby likely impacting their ability to comprehend and respond appropriately to stimuli within their PPS.…”
Section: Pps In Pathological Conditionsmentioning
confidence: 99%
“…[7][8][9] Autistic traits can be considered a sixth factor of personality in addition to the Big Five. 10,11 Increasing numbers of studies have found that autistic traits are prevalent in the general population, [12][13][14] indicating that the construct of autism might form a continuum in the general population based on traitlike characteristics. 15 More and more studies have demonstrated the continuum model.…”
Section: Introductionmentioning
confidence: 99%